Difference between revisions of "022 Sample Final A, Problem 1"
Jump to navigation
Jump to search
(8 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
− | <span class="exam">Find all first and second partial derivatives of the following function, and demostrate that the mixed second partials are equal for the function <math> f(x, y) = \frac{2xy}{x-y}.</math> | + | <span class="exam">Find all first and second partial derivatives of the following function, and demostrate that the mixed second partials are equal for the function <math style="vertical-align: -17px"> f(x, y) = \frac{2xy}{x-y}.</math> |
+ | |||
+ | |||
+ | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Foundations: | ||
+ | |- | ||
+ | |1) Which derivative rules do you have to use for this problem? | ||
+ | |- | ||
+ | |2) What is the partial derivative of <math style="vertical-align: -4px">xy</math>, with respect to <math style="vertical-align: 0px">x</math>? | ||
+ | |- | ||
+ | |- | ||
+ | |Answers: | ||
+ | |- | ||
+ | |1) You have to use the quotient rule and product rule. The quotient rule says that | ||
+ | ::<math style="vertical-align: 0px">\frac{\partial}{\partial x} \left(\frac{f(x)}{g(x)}\right) = \frac{f'(x)g(x) - g'(x)f(x)}{g(x)^2},</math> | ||
+ | so | ||
+ | ::<math style="vertical-align: 0px">\frac{\partial}{\partial x} \left(\frac{x^2}{x + 1}\right) = \frac{2x(x + 1) - x^2}{(x + 1)^2}.</math> | ||
+ | The product rule says | ||
+ | ::<math style="vertical-align: 0px">\frac{\partial}{\partial x} f(x)g(x) = f'(x)g(x) + g'(x)f(x). </math> | ||
+ | This means | ||
+ | ::<math style="vertical-align: 0px">\frac{\partial}{\partial x} [x(x + 1)] = (x + 1) + x. </math> | ||
+ | |- | ||
+ | |2) The partial derivative is <math style="vertical-align: -4px">y</math>, since we treat anything not involving <math style="vertical-align: 0px">x</math> as a constant and take the derivative with respect to <math style="vertical-align: 0px">x</math>. In more detail, we have | ||
+ | ::<math style="vertical-align: 0px">\frac{\partial}{\partial x} xy \,=\, y\frac{\partial}{\partial x} x \,=\, y.</math> | ||
+ | |} | ||
+ | |||
+ | '''Solution:''' | ||
+ | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Step 1: | ||
+ | |- | ||
+ | |First, we start by finding the first partial derivatives. So we have to take the partial derivative of <math style="vertical-align: -4px">f(x, y)</math> with respect to <math style="vertical-align: 0px">x</math>, and the partial derivative of <math style="vertical-align: -4px">f(x, y)</math> with respect to <math style="vertical-align: -4px">y</math>. This gives us the following: | ||
+ | |- | ||
+ | | | ||
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\frac{\partial}{\partial x} f(x, y)} & = & \displaystyle{\frac{\partial}{\partial x} \left( \frac{2xy}{x - y}\right)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{2y(x - y) -2xy}{(x - y)^2}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{-2y^2}{(x - y)^2}.} | ||
+ | \end{array}</math> | ||
+ | |- | ||
+ | |This gives us the derivative with respect to <math style="vertical-align: 0px">x</math>. To find the derivative with respect to <math style="vertical-align: -4px">y</math>, we do the following: | ||
+ | |- | ||
+ | | | ||
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\frac{\partial}{\partial y}f(x, y)} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{2xy}{x - y}\right)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{2x(x - y) +2xy}{(x - y)^2}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{2x^2}{(x - y)^2}.} | ||
+ | \end{array}</math> | ||
+ | |} | ||
+ | |||
+ | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Step 2: | ||
+ | |- | ||
+ | |Now we have to find the 4 second derivatives, We have | ||
+ | <br> | ||
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\frac{\partial^2f(x,y)}{\partial x^2}\,=\,\frac{\partial}{\partial x} \left(\frac{\partial f(x, y)}{\partial x}\right)} & = & \displaystyle{\frac{\partial}{\partial x}\left(\frac{-2y^2}{(x - y)^2}\right)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{0 - 2(x - y)(-2y^2)}{(x - y)^4}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{4xy^2 - 4y^3}{(x - y)^4}.} | ||
+ | \end{array}</math> | ||
+ | |- | ||
+ | |Also, | ||
+ | <br> | ||
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\frac{\partial^2f(x,y)}{\partial y\partial x}\,=\,\frac{\partial}{\partial y} \left(\frac{\partial f(x, y)}{\partial x}\right)} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{-2y^2}{(x - y)^2}\right)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{-4y(x - y)^2 -4y^2(x - y)}{(x - y)^4}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{-4y(x^2 - 2xy + y^2) - 4xy^2 + 4y^3}{(x - y)^4}}\\ | ||
+ | & = & \displaystyle{\frac{4xy^2 - 4x^2y}{(x - y)^4}.} | ||
+ | \end{array}</math> | ||
+ | |- | ||
+ | |Showing the equality of mixed partial derivatives, | ||
+ | <br> | ||
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\frac{\partial^2f(x,y)}{\partial x\partial y}\,=\,\frac{\partial}{\partial x} \left(\frac{\partial f(x, y)}{\partial y}\right)} & = & \displaystyle{\frac{\partial}{\partial x}\left(\frac{2x^2}{(x - y)^2}\right)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{4x(x - y)^2 -2(x - y)2x^2}{(x - y)^4}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{4x(x^2 - 2xy + y^2) -4x^3+ 4x^2y}{(x - y)^4}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{4xy^2 -4x^2y}{(x - y)^4}.} | ||
+ | \end{array}</math> | ||
+ | |- | ||
+ | |Finally, | ||
+ | <br> | ||
+ | ::<math>\begin{array}{rcl} | ||
+ | \displaystyle{\frac{\partial^2f(x,y)}{\partial y^2}\,=\,\frac{\partial}{\partial y} \left(\frac{\partial f(x, y)}{\partial y}\right)} & = & \displaystyle{\frac{\partial}{\partial y}\left(\frac{2x^2}{(x - y)^2}\right)}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{0 + 2(x - y)(2x^2)}{(x - y)^4}}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{4x^3 - 4x^2y}{(x - y)^4}.} | ||
+ | \end{array}</math> | ||
+ | |} | ||
+ | |||
+ | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
+ | !Final Answer: | ||
+ | |- | ||
+ | |The first partial derivatives are: | ||
+ | ::<math>\displaystyle{\frac{\partial}{\partial x} f(x, y) = \frac{-2y^2}{(x - y)^2}, \qquad | ||
+ | \frac{\partial}{\partial y} f(x, y) = \frac{2x^2}{(x - y)^2}.}</math> | ||
+ | |- | ||
+ | |The second partial derivatives are: | ||
+ | ::<math>\frac{\partial^{2}f(x,y)}{\partial x^{2}}\,=\,\frac{4xy^{2}-4y^{3}}{(x-y)^{4}}, | ||
+ | \qquad\frac{\partial^{2}f(x,y)}{\partial x\partial y}\,=\,\frac{\partial^{2}f(x,y)}{\partial y\partial x}\,=\,\frac{4xy^{2}-4x^{2}y}{(x-y)^{4}},\qquad\frac{\partial^{2}f(x,y)}{\partial y^{2}}\,=\,\frac{4x^{3}-4x^{2y}}{(x-y)^{4}}.</math> | ||
+ | |} | ||
+ | [[022_Sample_Final_A|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 08:20, 7 June 2015
Find all first and second partial derivatives of the following function, and demostrate that the mixed second partials are equal for the function
Foundations: |
---|
1) Which derivative rules do you have to use for this problem? |
2) What is the partial derivative of , with respect to ? |
Answers: |
1) You have to use the quotient rule and product rule. The quotient rule says that
so The product rule says This means |
2) The partial derivative is , since we treat anything not involving as a constant and take the derivative with respect to . In more detail, we have
|
Solution:
Step 1: |
---|
First, we start by finding the first partial derivatives. So we have to take the partial derivative of with respect to , and the partial derivative of with respect to . This gives us the following: |
|
This gives us the derivative with respect to . To find the derivative with respect to , we do the following: |
|
Step 2: |
---|
Now we have to find the 4 second derivatives, We have
|
Also,
|
Showing the equality of mixed partial derivatives,
|
Finally,
|
Final Answer: |
---|
The first partial derivatives are:
|
The second partial derivatives are:
|